Effectiveness of Adopting Cloud-Based E-Learning at Qassim University. (1st December 2020) - Alajlan, Norah; Hadwan, Mohammed; Ibrahim, Dina M
Abstract: The growth of cloud computing (CC) is noticeable in Saudi Arabia, especially in educational institutions. To have an effective E-learning platform, CC is widely used due to its capabilities. This research studying the factors affects the adoption of cloud-based E-learning at Qassim University (QU) from the student's perspective. A model proposed to measure the effectiveness of the current E-learning system at QU and to identify the significant factors required to encourage students to keep using it. The proposed model includes the theory of motivation, the theory of technology acceptance model and characteristics of CC. Data collected from 114 students analyzed using SmartPLS. Results show the perceived ease of use and extrinsic motivation are significant factors that means have high effects on the intention to use (ITU). While other factors such as availability, collaboration and intrinsic motivation are insignificant that have less or no effect on the ITU cloud-based E-learning.